2021
DOI: 10.3390/ijms22179125
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Immune Checkpoint Inhibitor-Mediated Anti-Cancer Immunity by Intranasal Treatment of Ecklonia cava Fucoidan against Metastatic Lung Cancer

Abstract: Although fucoidan, a well-studied seaweed-extracted polysaccharide, has shown immune stimulatory effects that elicit anticancer immunity, mucosal adjuvant effects via intranasal administration have not been studied. In this study, the effect of Ecklonia cava-extracted fucoidan (ECF) on the induction of anti-cancer immunity in the lung was examined by intranasal administration. In C57BL/6 and BALB/c mice, intranasal administration of ECF promoted the activation of dendritic cells (DCs), natural killer (NK) cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…Fucoidan extracted from three species of algae, among them Fucus vesiculosus , promoted proliferation and activity of ex vivo PBMCs and potentiated anti-PD-1 effects [ 68 ]. Intranasal administration of Ecklonia-cava -extracted fucoidan enhanced anti-PD-L1 mediated anti-cancer activities against melanoma and carcinoma tumor growth in lungs [ 69 ]. Fucoidan of Luminaria japonica enhanced anticancer efficacy of anti-PD-L1 antibodies against Lewis lung carcinoma [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fucoidan extracted from three species of algae, among them Fucus vesiculosus , promoted proliferation and activity of ex vivo PBMCs and potentiated anti-PD-1 effects [ 68 ]. Intranasal administration of Ecklonia-cava -extracted fucoidan enhanced anti-PD-L1 mediated anti-cancer activities against melanoma and carcinoma tumor growth in lungs [ 69 ]. Fucoidan of Luminaria japonica enhanced anticancer efficacy of anti-PD-L1 antibodies against Lewis lung carcinoma [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these was the fucoidan from Ecklonia cava (ECF), administered intranasally in mice, which promoted the activation of dendritic cells, natural killer cells (NK) and T cells. In addition, it was found that intranasal injection of ECF enhanced the antitumor effect of PD-L1 antibodies on melanoma B16 and carcinoma CT-26 in lung metastases, showing that ECF could function as an adjuvant enhancing the immunotherapeutic effect of immune checkpoint inhibitors against metastatic lung cancer [ 25 ].…”
Section: Antitumor Activitymentioning
confidence: 99%
“…The alga Ecklonia cava is an edible medicinal food that is widely consumed in Korea and Japan for its reported multiple health benefits that include anti-cancer [ 7 ], anti-diabetes [ 8 ], anti-inflammatory [ 9 ], and anti-obesity [ 10 ] properties. These studies from two publications suggest that the alga and isolated bioactive compounds might be safe for human consumption.…”
Section: Introductionmentioning
confidence: 99%